Performance evaluation of solar cabinet and tunnel dryer for drying agro-commodity: A comparative study - Pagar, Jitendra; Patil, Rajendra; Darekar, Deepak; Ingale, Sachin; Singh, Shivnath (Journal of Postharvest Technology, 2024)
Solar drying is the traditional method of preserving fruits, crops and vegetables. It is an alternate  strategy for avoiding a natural resource deficit. However, traditional sun drying degrades food quality  and is ineffective in preventing dust, other insects, or birds. For this reason, this article represents  suitable post-harvest solar dryer technology for 4kg of tomato drying. In this study, two different  solar dryers, viz. indirect solar cabinet dryer (SCD) and direct solar tunnel dryer (STD) of the same  aperture area, were examined simultaneously under the environmental conditions of Nashik, India.  After 12 hours of drying time in two days experiment, the moisture content of tomato slices inside of  tunnel dryer is 15.1% (w.b.); meanwhile, the cabinet dryer is still 53% (w.b.). The result showed that  both dryers produce a drying air temperature of 45-670C, which is suitable for drying almost all agro commodities. The average thermal efficiency was 17% & 14% for solar cabinet dryers and 30% &  29% for solar tunnel dryers, respectively, in two days experiment. According to these results, solar  tunnel dryer shows better performance in terms of average drying air temperature, thermal  efficiency, moisture removal rate and quality of the dried product compared to solar cabin
Keywords: Solar dryer; efficiency,; tomato,; moisture content.